Scripting the Black masculine body : identity, discourse, and racial politics in popular media - Jackson, Ronald L., 1970- (SUNY series, negotiating identity., 2006)
"Scripting the Black Masculine Body traces the origins of Black body politics in the United States and its contemporary manifestations in popular cultural productions. From early blackface cinema through contemporary portrayals of the Black body in hip-hop music and film, Ronald L. Jackson II examines how African American identities have been socially constructed, constituted, and publicly understood, and argues that popular music artists and film producers often are complicit with Black body stereotypes. Jackson offers a communicative perspective on body politics through a blend of social scientific and humanities approaches and offers possibilities for the liberation of the Black body from its current ineffectual and paralyzing representations."--Jacket